2012
DOI: 10.1186/1475-2891-11-44
|View full text |Cite
|
Sign up to set email alerts
|

The inclusion of a partial meal replacement with or without inulin to a calorie restricted diet contributes to reach recommended intakes of micronutrients and decrease plasma triglycerides: A randomized clinical trial in obese Mexican women.

Abstract: Background Obesity is a major public health problem in many poor countries where micronutrient deficiencies are prevalent. A partial meal replacement may be an effective strategy to decrease obesity and increase micronutrient intake in such populations. The objective was to evaluate the efficacy of a partial meal replacement with and without inulin on weight reduction, blood lipids and micronutrients intake in obese Mexican women. Methods In a randomized controlled clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
2
34
2
8
Order By: Relevance
“…Tovar et al (23) reported that a soluble dietary fibre (inulin) can decrease the content of plasma TAG, which was inconsistent with our results. Besides, no relationship was found between plasma lipids and higher BW gain in lean rats.…”
Section: Discussioncontrasting
confidence: 57%
“…Tovar et al (23) reported that a soluble dietary fibre (inulin) can decrease the content of plasma TAG, which was inconsistent with our results. Besides, no relationship was found between plasma lipids and higher BW gain in lean rats.…”
Section: Discussioncontrasting
confidence: 57%
“…See table 1 for characteristics of the 19 RCTs included [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], of which 9 were parallel RCTs and 10 trials had a crossover design. Four RCTs involving 232 participants were carried out in children [12,22,24,29], and the remaining 15 RCTs involving 545 participants were carried out in adults.…”
Section: Resultsmentioning
confidence: 99%
“…Harrold et al [18] conducted a 4-arm, crossover RCT to assess the effects of consumption of an inulin-based soluble fermentable fiber, patented herb extract Yerbe Maté, Guarana and Damiana (YGD) and both combined compared with a control product. The study by Tovar et al [28] was a 4-arm RCT that assessed the effects of inulin, partial meal replacement, both combined and a control product. However, here we only report data that fulfilled the inclusion criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since high energy dense foods have the lowest satiating capacity even if they usually have a high palatability, 44 the high level of proteins and fibers and the high palatability, despite the low sugar content, of these new ultra-processed foods, are important features which contribute to both food reward and satiety. 45 The tendency to prefer sugary fatty foods over savory foods is considered innate and universal and finds its roots in very important adaptive processes: a bitter taste is considered predictive of toxicity and then avoided (alkaloids, glycosides and other toxins have a bitter taste), whilst the sweet taste is associated with energy and nourishment 46 . Although it is recognized that the VLCKDs lead to greater weight losses compared to a low-calorie balanced diet at least in the short term, 47 subjects with a sweet food preference may not adhere to this diet because of the lack of their prefered taste.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, participants maintained a constant foods supply, without changing their usual eating habits. *** FIGURE 1 HERE*** Fingertip capillary blood samples were collected in the fasted state and after 15,30,45,60,90, and 120 min after starting to eat, changing the finger each time to avoid traumatization of the skin. The puncture was performed with the lancet Accu-Check Safe-T-Pro Plus (Roche Diagnostics, Basel, Switzerland) and blood was collected directly and immediately analysed using test strip Reflotron ® Glucose.…”
Section: Methodsmentioning
confidence: 99%